close
此文章來自奇摩知識+如有不便請留言告知
標題:
Binomial Thm.
發問:
Find the constant term in the expansion : (x - 2/x^2)^3(3x + 1/x)^4
最佳解答:
Degree of each term of (x-2/x^2)^3: 3,0,-3,-6 Degree of each term of (3x+1/x)^4: 4,2,0,-2,-4 Therefore it is trivial that there is only 1 constant term in the expansion of(x-2/x^2)^3(3x+1/x)^4: 3 * [x^2 * (-2/x^2)] * 6 * [(3x)^2 * (1/x)^2] =3 * -2x^2/x^2 * 6 * 9x^2/x^2 =3 * -2 * 6 * 9 =-324 2013-06-16 08:24:37 補充: Feel free to ask me for further questions.
其他解答:
Find the constant term in the expansion : (x-2/x^2)^3(3x+1/x)^4 Sol (x-2/x^2)^3(3x+1/x)^4 =(x^3-2)^3(3x^2+1)^4/x^10 10=6+4 C(3,2)*(-2)*C(4,2)*3^2 =3*(-2)*6*9 =-324A9A39959EDCC7BE3
文章標籤
全站熱搜
留言列表